The Evaluatıon Of Dıfferent Roughenıng Methods On The Retentıon Of Orthodontıc Bands - Enis Güray; Ali İhya Karaman (Galenos Yayinevi, 1996)
Many studies performed to tedermine the peculiarities of glass ionomer cements were showed that these cements protect the enamel surface better and also have better retentive strength when compared to the other orthodontic cements. However, in fact of these adequacies, tensile tests were also showed that significantly more bands cemented with the glass ionomer failed at the cement band interface, leaving the cement adhering to the tooth. In the present study, the effects of different roughening methods on the retention of orthodontic bands were evaluated. For this purpose, a micro-sandblasting with 90 micron aluminium oxide powder, a tungsten carbide bur and a green stone were applied on the retentive surfaces of the 45 pre-formed upper premolar bands. As a control group 15 pre-formed uper premolar bands, cemented with Ketac Cem, were used. The bands of the control group were not subjected to the roughening and all 60 bands of the study were also cemented by Ketac Cem. By means of Testometric Migro 500 Universal machine, four groups of the stduy, each consisting of 15 bands, were subjected to a tensile load in KOSGEB Laboratory. The roughened band surfaces were also evaluated by means Jeol JSM 5200 electron microscope. The differences between groups were evaulated by using the variance analysis (ANOVA) and Duncan's Multiple Range Test. The failure site was judged subjectively: between cement and enamel, within the cement, or between cement and the band. The increase on the retention of the bands subjected to the roughening was found statistically significant (p<0.001) however, Duncan's Multiple Range Test was showed no significant differences among the retentive strengths of the three methods. However, electron micrographs were indicated that the roughened surfaces abraded with a tungsten carbide bur or a green stone were nor rough at all under higher magnifications. The appearance of roughness was caused by periodic ridges and grooves. In spite of this, on the micrographs of the roughened surfaces with micro-etcher were seen many homogeneous retentive surfaces with thousands of microscopic undercuts The failure site on all rough bands was observed at the cement-band interface, leaving the cement adhered to the band, oppositely to the control group where, following to the failure, the cement was observed adhered to the enamel surface. As a conclusion, all of the three roughening methods were found advisable on the retention of the orthodontic bands and preferable for their practical application onda their lower cost/prizes.